2015
DOI: 10.1128/jvi.02503-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mutagenesis of the Adeno-Associated Virus 5 Sialic Acid Binding Region

Abstract: As a genus, the dependoviruses use a diverse group of cell surface carbohydrates for attachment and entry. Despite the fact that a majority of adeno-associated viruses (AAVs) utilize sialic acid (SIA) for binding and transduction, this virus-carbohydrate interaction is poorly understood. Utilizing X-ray crystallography, two SIA binding regions were mapped for AAV5. The first site mapped to the depression in the center of the 3-fold axis of symmetry, while the second site was located under the ␤HI loop close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…Structural alignment showed that AAV4 K492 and K503, which superpose with AAV1 S499 and T504, are adjacent to the SIA binding residue N500 and W503 on AAV1. AAV5 binds to SIA by M569, A570, T571, A581, G583, T584, Y585, N586, and L587 (65). However, none of these AAV5 residues is close to the SIA binding site on AAV1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural alignment showed that AAV4 K492 and K503, which superpose with AAV1 S499 and T504, are adjacent to the SIA binding residue N500 and W503 on AAV1. AAV5 binds to SIA by M569, A570, T571, A581, G583, T584, Y585, N586, and L587 (65). However, none of these AAV5 residues is close to the SIA binding site on AAV1.…”
Section: Discussionmentioning
confidence: 99%
“…This MAb inhibits infection at a postnuclear entry step. For AAV5, mutation of its SIA binding site has also been shown to create variants able to escape from antibody recognition (65), again pointing to a neutralization mechanism involving receptor attachment blockage. In the example of AAV8, its ADK8 MAb blocks infection at a post-cell/prenuclear-entry step, suggesting a block in cellular trafficking (58).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that neutralization by ADK5b is due to the occlusion of residues on the wall of the 3-fold protrusion facing the 5-fold axis and/or the DE loop forming the 5-fold cylinder, which are unique to the epitope for this MAb. Significantly, the SIA A site has been implicated in SIA-dependent cellular transduction (77,80). It is possible that the binding of ADK5b to the outer wall of protrusions has an effect on this function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that AAV5 can utilize sialic acid (SIA) as a receptor to infect cells (74)(75)(76), and two SIA binding sites, A and B, have been described (77). The A site is at the center of the 3-fold axis and includes residues 569, 570, 571, and 583 to 587; the B site is located under the HI loop close to the 5-fold axis and includes residues 277, 279, 280, 350 to 354, 359, 361 to 363, 533, and 650 to 652.…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acid is required for AAV5 binding and infection (Walters et al, 2004). Afione and collaborators have recently identified AAV5 sialic acid binding region (Afione et al, 2015),…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%